Expression of GATA and POU transcription factors during the development of the planktotrophic trochophore of the polychaete serpulid Hydroides elegans. Issue 4 (July 2016) - Wong, Kimberly Suk‐Ying; Arenas‐Mena, Cesar
SUMMARY: The expression of transcription factors with endodermal and mesodermal roles in bilaterians is characterized during the development of Hydroides elegans, a serpulid polychaete with planktotrophic trochophore. GATA 4/5/6 is expressed in endodermal and mesodermal precursors during embryogenesis and in the midgut of trochophore larvae. HeGATA1/2/3a is expressed in animal hemisphere blastomeres 1d121 and 1d122, in dorsal ectoderm and in 4d endomesodermal derivatives that maintain their expression in trochophore larvae. HeGATA1/2/3b is not expressed during embryogenesis, but in several regions of the larva during postembryonic development. During very early gastrulation, Brn1/2/4 is first expressed in cells associated with the prospective oral/foregut side of the blastopore, and during larval development in 4d blastomere descendants. Comparison with orthologs in other metazoans suggests ancestral expression of GATA4/5/ 6 in the midgut of the last common ancestor of protostomes and deuterostomes. The conserved expression of Brn1/2/4 in the foregut precursors of Hydroides and sea urchins suggests an ancestral role in patterning the tripartite gut of planktotrophic larvae. Broader analysis of these and other regulatory genes reveals variability of developmental gene expression among polychaetes with lecithotrophic larvae, suggesting that they are evolutionarily derived from polychaetes with planktotrophic larvae.